Fama and French Five- Factor Study of Stock Market in Indonesia - Bryan Buditomo; Steven Candra; Tessa Vanina Soetanto (International Journal of Organizational Behavior and Policy, 2024)
In general, contemporary finance theories agree that the Fama and French Five-Factor model provides a more comprehensive explanation for average stock returns compared to its predecessors. Previous research on the five-factor model in Indonesia has yielded inconclusive results, and none of the studies has attempted to compare the significance of the five factors over shorter and longer periods, or even within shorter periods. As a result, the researchers of this study endeavor to ascertain the importance of the five elements – the profitability (RMW), market, size (SMB), profitability (RMW), book-to-market (HML), and investment (CMA) factors – to an excess return on the portfolio over shorter and longer periods. The findings indicate that SMB and CMA factors exhibit statistically insignificant, significantly negative, and significantly positive correlations with excess portfolio return, respectively, over the three shorter periods and the longer period. A significant negative correlation is observed between the HML factor and excess portfolio return over the longer period, while the relationship is deemed insignificant over the three shorter periods. No significant relationship was found between the RMW factor and excess portfolio return over the (2005-2019) period and two (2010-2014, 2015-2019) periods, but one shorter period is significantly positive.